Development of Educational Games as a Learning Arithmetic Operations with The Sprint Design Method - Muchamad Arif; Etistika Yuni Wijaya; Ray Albian; Juwita Nurqomariah (Komunitas Dosen Indonesia, 2024)
The development of information and communication technology (ICT) has had a significant impact on various aspects of life, including education. The use of ICT-based learning media can make the learning process more engaging, effective, and efficient. One trending form of learning media is educational games. Educational games combine educational content with computer game elements to create an enjoyable and engaging learning experience. The main advantage of educational games is their ability to illustrate real-world problems and encourage players to actively seek information while improving their skills and understanding. This study aims to develop Android-based learning media in the form of educational games using the Sprint Design methodology. This method includes five phases: understanding, diverging, deciding, prototyping, and validating. The understanding phase involves curriculum analysis and user needs, while the diverging phase produces strategies and design sketches. The deciding phase selects the best ideas, the prototyping phase builds the initial model, and the validating phase includes testing by content and media experts. The results indicate that the educational game is effective in increasing students' interest and understanding of mathematics. Trials showed high validation scores from content and media experts, as well as positive feedback from students. The game is deemed feasible as a learning medium and can enhance educational quality with a user-friendly interface. Ongoing and innovative development of educational games is necessary to improve education quality in Indonesia.